DNA damage and postural balance in multiple sclerosis patients - Karla Mendonça Menezes; Thaís Doeler Algarve; Fábio Saraiva Flôres; Ivana Beatrice Mânica Cruz; Fernando Copetti; Aron Ferreira Silveira
Abstract Introduction: Multiple Sclerosis (MS) is a chronic inflammatory disease characterized by infiltration of inflammatory cells on the Central Nervous System (CNS). There is evidence that cumulative DNA damage can contribute to various mechanisms underlying MS lesions. Changes in postural balance are frequent observations in subjects with MS. Objective: Evaluated the DNA damage index (DDI)) and postural balance in patients with MS. Methods: A case-control study was conducted with 28 subjects matched for sex, age, and body mass index, divided into MS group and control. The DDI was assessed by comet assay and postural balance through recording the body oscillations of the center of pressure (COP), in the anterior-posterior and lateral middle directions. Results: Showed higher DDI in MS patients (21.3 ± 4.8) than controls (7.9 ± 6.1). Significant differences between groups were also noted in postural control parameters. The wider ranges of postural sway were observed in the MS group. The associations between DDI and postural control parameters showed weak, but significant correlations. No associations were found between DDI and time of diagnosis of MS. Conclusion: People with MS had higher DDI and larger body oscillations than healthy individuals.